ARE THERE LAWS AND POLICIES PROTECTING PEOPLE INFECTED AND AFFECTED BY HIV/AIDS IN SOUTHERN AFRICA? AN UPDATE OF A REVIEW OF THE EXTENT TO WHICH COUNTRIES WITHIN THE SOUTH AFRICAN DEVELOPMENT COMMUNITY HAVE IMPLEMENTED THE HIV/AIDS AND HUMAN RIGHTS INTERN - Ann Strode; Brenda Grant; Suhayfa Bhamjee (Obiter, 2021)
A review published in 2007 of the extent to which countries in the Southern African Development Community (SADC) region were implementing the HIV/AIDS and Human Rights International Guidelines was completed in 2006.  In summary the review found that almost all SADC countries were committed, in principle, to responding to HIV and AIDS as a human rights issue because most had begun to implement key legal and policy reforms based on human rights principles. However, at the same time the criminal law was being used to respond to HIV in a coercive manner, thus undermining human rights-based responses. Finally, there were a number of emerging human rights issues that needed to be addressed, including a lack of access to antiretroviral treatment and the undermining of civil and political rights by policy reforms aimed at enhancing access to HIV testing and treatment. This note is an update of the findings of the review published in 2007. It critically examines the progress, or lack of it, made in the last three years by comparing the legislative and policy steps taken by SADC countries in responding to the HIV epidemic.